Nursing Interventions in A Diabetic Patient with Urinary Tract Infection and Renal Complication - Vásquez-Morán, Bertha Alejandrina; Zurita-Desiderio, Mariuxi Johanna; Quijije-Chavez, Vilma Rocío; Ortega, Fanny Isabel Arteaga (South Eastern European Journal of Public Health, 2024)
Urinary tract infection (UTI) is a common condition caused by the entry of bacteria or other infectious agents into the urinary system. If not properly treated, it can lead to serious renal complications, such as pyelonephritis, a bacterial infection of the kidneys that can cause permanent damage and even kidney failure. This case study focused on the careful application of nursing interventions used to successfully manage the care of a geriatric female patient with diabetes mellitus and urinary tract infections. Through thorough research and analysis of the data collected, an effective treatment approach to address UTIs was developed. During the initial phase of this study, specific patient-related data were collected, taking into account the unique risk factors that affect older women, such as menopause, and hormonal changes that may predispose to UTI. These data were used as the basis for designing evidence-based personalized care interventions. Patient-centered care proved to be highly beneficial; significant improvements in her overall health and well-being were observed. Preventive measures to reduce recurrence of UTIs were implemented through a multidisciplinary approach involving physicians, nurses, and nutritionists. It is critical to emphasize that this experience provided a valuable knowledge base that can be extrapolated to the care of other older women who will face similar problems. The integration of personalized, evidence-based strategies in the care of geriatric patients with diabetes and urinary tract infection problems is essential to improve their quality of life and reduce long-term complications.